2013
DOI: 10.1093/jac/dkt483
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetic interaction of rifapentine and raltegravir in healthy volunteers

Abstract: The increased raltegravir exposure observed with once-weekly rifapentine was safe and tolerable. Once-weekly rifapentine can be used with raltegravir to treat latent tuberculosis infection in patients who are infected with HIV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(26 citation statements)
references
References 31 publications
1
25
0
Order By: Relevance
“…[15, 16] Furthermore, additional studies have demonstrated that once-weekly rifapentine may be given with the integrase strand transfer inhibitor raltegravir. [17] Although studies of the effectiveness of 3HP when given with efavirenz-or raltegravir-based antiretroviral therapy are needed, these pharmacokinetic studies suggest that such regimens can be given concomitantly. Such effectiveness studies would likely include persons with lower CD4+ lymphocyte counts.…”
Section: Discussionmentioning
confidence: 99%
“…[15, 16] Furthermore, additional studies have demonstrated that once-weekly rifapentine may be given with the integrase strand transfer inhibitor raltegravir. [17] Although studies of the effectiveness of 3HP when given with efavirenz-or raltegravir-based antiretroviral therapy are needed, these pharmacokinetic studies suggest that such regimens can be given concomitantly. Such effectiveness studies would likely include persons with lower CD4+ lymphocyte counts.…”
Section: Discussionmentioning
confidence: 99%
“…8789 Highdose daily rifapentine can be safely administered with efavirenz, allowing the 3-month regimen to be administered with efavirenz-based ART. 80,90 Although raltegravir exposure was increased when administered with once-weekly rifapentine, 91 the regimen was well tolerated, supporting use of raltegravir-based regimens. There are no pharmacokinetic data on rifapentine with dolutegravir.…”
Section: Interface Of Art and Oismentioning
confidence: 92%
“…Despite this, no clinically meaningful effect on efavirenz exposure was seen in 87 patients receiving a four-week course of daily rifapentine for TB prevention in ACTG 5279 23 . Rifapentine increased raltegravir exposure in a healthy volunteer study, but this was safe and tolerable; therefore, once-weekly rifapentine can be used in HIV-infected patients on raltegravir 24 .…”
Section: New Applications Of Existing Drugsmentioning
confidence: 89%